Review of Literature: Neuromuscular Adaptations to Plyometrics - marc heinecke (International Universities Strength and Conditioning Association, 2021)
Plyometric exercises are a training stimulus that were developed in an attempt to bridge the gap between weight room muscular strength exercises and the speed or power needed on the track, field or court.  Verkhoshansky (2018) uses physics to describe his method of plyometrics where a falling body creates kinetic energy which, upon impact with the ground, causes a high degree of muscle tension.  The impact stimulates high threshold motor neurons and these, along with elastic energy, create the potential for an enhanced stretch shortening cycle with minimal amortization.  This modality of training is a well-established method to improve vertical jumping ability (Adams et al., and Fatourous et al., 2000), and sprinting abilities as well (Miller 1980; Chu 1983), however, there still seems to be confusion surrounding its application.   With most of the early research on plyometrics coming from Russia, a lot of the early information was lost in translation which lead to misapplication in the United States (Verkhoshansky, 2018). One clear example of this is in the execution of a drop jump versus a depth jump, and the appropriate height for each of these exercises (Verkhoshansky, 2018).   The depth jump was typically performed on a 75cm box, with a larger countermovement, and an end goal of jumping as high as possible, while the drop jump typically used 30-45cm, landing with stiff legs and a minimal countermovement, sought to minimize ground contact times through the usage of elastic energy, while maximizing vertical displacement (Verkhoshansky, 2018).              Researchers have shown that these exercises are capable of improving performance, but it has been hard to pinpoint the mechanism behind the adaptations.   Vershoshansky (2018) indicated that when depth jumps are incorporated into a training cycle, they actually replace the heavy squat, yet at the end of the cycle his athletes' squat maxes would increase.  This would indicate that improved strength and force production could be a driving force behind the improvements in running speed and jumping abilities.  Looking at this explanation, investigators might need to look at the neural aspects of movement including motor unit recruitment and increased muscle activation to find the process behind adaption and improved athletic performance as well as looking at the stretch-shortening cycle itself as the elastic energy minimizes the amortization phase.  Verkhoshansky (1979) believed the neuromuscular system's reaction to plyometric activity to be protective in nature and a result of either utilization of the stretch reflex, elastic energy recoil, or increased CNS activation due to rapid eccentric movements.  If a more precise channel for what creates the adaptation is found it may allow for better programming which would not only enhance the adaptation but could lead to a reduction in injury.   Therefore, the purpose of the review of literature is not to show that this modality of exercise can enhance athletic performance but, to gain an understanding on what mechanism drives the adaptation.